2020
DOI: 10.3390/ijms21197296
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis and Specific Expression of Transcription Factor Genes in the Root and Sporophyll of Dryopteris fragrans (L.) Schott

Abstract: Background: Dryopteris fragrans, which is densely covered with glandular trichomes, is considered to be one of the ferns with the most medicinal potential. The transcriptomes from selected tissues of D. fragrans were collected and analyzed for functional and comparative genomic studies. The aim of this study was to determine the transcriptomic characteristics of wild D. fragrans sporangium in tissues from the SR (root), SL (sporophyll), and TRL (sporophyll with glandular trichomes removed). Results: Cluster an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The gene fusion test of the RIE1 promoter with the β-glucuronidase (GUS) gene indicated that this is expressed in several plant tissues ( Xu & Li, 2003 ). Likewise, LOB domain-containing protein 21 gene was found associated with the development of glandular trichomes in plants ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gene fusion test of the RIE1 promoter with the β-glucuronidase (GUS) gene indicated that this is expressed in several plant tissues ( Xu & Li, 2003 ). Likewise, LOB domain-containing protein 21 gene was found associated with the development of glandular trichomes in plants ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among other TFs, APETALA2 (AP2) domain ABR1 -like genes and ethylene-responsive transcription factor ERF071 were significantly induced. ABR1 acts as a repressor of ABA ( Chen et al., 2020 ). However, ERF71 is believed to contribute to tolerance in anoxia stress condition by increasing anaerobic gene expression and adventitious root growth under hypoxia ( Licausi et al., 2010 ; Eysholdt-Derzsó and Sauter, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dryopteris fragrans (L.) Schott (D. fragrans), a deciduous perennial herb, belongs to family Dryopteridaceae and broadly distributes in Asia-temperate, Europe and North America [12,13]. Infusions and decoctions of its aerial parts are folk medicines that have been used in a wide range of curing fungal skin infections, such as dermatitis, rashes, psoriasis, and beriberi [14].…”
Section: Introductionmentioning
confidence: 99%